The relationship of pleural manometry with postthoracentesis chest radiographic findings in malignant pleural effusion - Chopra, A; Judson, M; Doelken, P; Maldonado, F; Rahman, N; Huggins, J (Elsevier, 2019)
BACKGROUND:Both elevated pleural elastance (E-PEL) and radiographic evidence of incomplete lung expansion following thoracentesis have been used to exclude patients with a malignant pleural effusion (MPE) from undergoing pleurodesis. This article reports on a cohort of patients with MPE in whom complete drainage was attempted with pleural manometry to determine the frequency of E-PEL and its relation with postthoracentesis radiographic findings. METHODS:Seventy consecutive patients with MPE who underwent therapeutic pleural drainage with pleural manometry were identified. The pressure/volume curves were constructed and analyzed to determine the frequency of E-PEL and the relation of PEL to the postthoracentesis chest radiographic findings. RESULTS:E-PEL and incomplete lung expansion were identified in 36 of 70 (51.4%) and 38 of 70 (54%) patients, respectively. Patients with normal PEL had an OR of 6.3 of having complete lung expansion compared with those with E-PEL (P = .0006). However, 20 of 70 (29%) patients exhibited discordance between postprocedural chest radiographic findings and the pleural manometry results. Among patients who achieved complete lung expansion on the postdrainage chest radiograph, 9 of 32 (28%) had an E-PEL. In addition, PEL was normal in 11 of 38 (34%) patients who had incomplete lung expansion as detected according to the postthoracentesis chest radiograph. CONCLUSIONS:E-PEL and incomplete lung expansion postthoracentesis are frequently observed in patients with MPE. Nearly one-third of the cohort exhibited discordance between the postprocedural chest radiographic findings and pleural manometry results. These findings suggest that a prospective randomized trial should be performed to compare both modalities (chest radiograph and pleural manometry) in predicting pleurodesis outcome.